2011
DOI: 10.2298/jsc100721051s
|View full text |Cite
|
Sign up to set email alerts
|

Removal of orange 16 reactive dye from aqueous solutions by waste sunflower seed shells

Abstract: In this work, the use of an agro-industrial waste, i.e., sunflower seed shells, was investigated as a sorbent for the removal of Orange 16 reactive dye from aqueous environments. Batch experiments were performed as a function of pH, sorbent dose, dye concentration, temperature and contact time. The percent dye removal increased with increasing sorbent dose and temperature of the aqueous solution, and decreased with increasing dye concentration; the required contact time was five hours. The Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…Each of the design parameters was investigated at five different values as shown in Table 2. We designed our experiments to obtain a quadratic model consisting of 2 4 trials plus a star configuration and six center points. Then, the results of the CCD were used to fit a quadratic equation by a multiple regression procedure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each of the design parameters was investigated at five different values as shown in Table 2. We designed our experiments to obtain a quadratic model consisting of 2 4 trials plus a star configuration and six center points. Then, the results of the CCD were used to fit a quadratic equation by a multiple regression procedure.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the discharge of dye-containing effluents into water is undesirable due to their color and because decomposition products of many dyes have toxic, carcinogenic, or mutagenic effects on living organisms. For example, it was reported that some carcinogens such as benzidine, naphthalene, and other aromatic compounds, originated from dyes [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pada industri tersebut, zat warna ini memiliki berbagai polutan pada proses yang berbeda-beda [2]. Air limbah tekstil mencakup berbagai macam pewarna dan tambahan bahan kimia yang membuat tantangan lingkungan untuk industri tekstil tidak hanya untuk limbah cair tetapi juga komposisi kimianya dan polusi utama dalam air limbah tekstil berasal dari pencelupan dan finishing [3].…”
Section: Pendahuluanunclassified
“…These negative impacts mainly attributed to the nonbiodegradable nature of the persistent organic dyes as well as their high colour intensity and are able to reduce aquatic diversity by blocking the passage of sunlight through the water [12]. In particular, the discharge of persistent organic dye effluents into the natural water resources or wastewater treatment systems is undesirable because most of these organic dyes released and their breakdown products are very toxic, carcinogenic, or mutagenic to life forms mainly due to the carcinogens, such as benzidine, naphthalene, and other aromatic compounds in the structure of persistent organic dyes [5,13,14]. These pollutants can cause irritation of the eyes, skin, respiratory tract, sore throat, asthma, and allergic contact dermatitis [15].…”
Section: Introductionmentioning
confidence: 99%